2012
DOI: 10.1111/j.1600-0536.2011.02046.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch test characteristics of patients referred for suspected contact allergy of the feet-retrospective 10-year cross-sectional study of the IVDK data

Abstract: Chromium compounds and adhesives were the most common causes of allergic contact dermatitis among our foot patients. Psoriasis should be considered, particularly when the hands are concomitantly affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(77 citation statements)
references
References 26 publications
11
62
3
1
Order By: Relevance
“…5 Several articles beyond the ESSCA have, however, reported on contact allergies linked to specific body sites, such as the hands, legs, feet, and face. [6][7][8][9][10][11][12] One publication reported on the frequency of dermatitis at specific body sites, but not on specific contact allergies. 13 Contact allergies linked to various body sites in patients diagnosed with allergic contact dermatitis (ACD) from the ESSCA database have not yet been reported.…”
Section: Previous Analyses Of the European Surveillance System On Conmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Several articles beyond the ESSCA have, however, reported on contact allergies linked to specific body sites, such as the hands, legs, feet, and face. [6][7][8][9][10][11][12] One publication reported on the frequency of dermatitis at specific body sites, but not on specific contact allergies. 13 Contact allergies linked to various body sites in patients diagnosed with allergic contact dermatitis (ACD) from the ESSCA database have not yet been reported.…”
Section: Previous Analyses Of the European Surveillance System On Conmentioning
confidence: 99%
“…11 The fact that allergy to HICC, together with allergies to other fragrances, was least often seen in patients with ACD of the feet is in accordance with previous studies. 10 Formaldehyde is often found in cosmetics. In a recent Danish study, it was mostly found in creams, shampoos, and soaps.…”
Section: Specific Allergensmentioning
confidence: 99%
“…Multiple allergens (e.g. in shoes and socks, such as dyes, glues, chromium as a tanning agent, and others) may playsomeroleassensitizers, 30 incombinationwithaggravatingfactors such as occlusion, sweating and friction. Although the face is an important site, with a partly characteristic spectrum of allergens, 31 facial contact dermatitis is not related to PS, as in the study of Carlsen et al 25 Other anatomical sites considered in our study, but not in previous analyses, are not associated with a markedly increased or decreasedriskofPS.…”
Section: -Chloro-2-methyl-isothiazol-3(2h)-one and 2-methylisothiazomentioning
confidence: 99%
“…Patch test characteristics of feet ACD in European patients were reported in the largest study to date of this condition by Landeck et al covering the 2001 to 2010 period. 5 Data reported from the European Surveillance System on Contact Allergies (ESSCA) database from 2009 to 2014 showed that in Spain, ACD with the feet as the single anatomical site was most common (7.7%) among eight countries. 6 To assess the spectrum of allergens related to feet dermatitis in Spain, we conducted a retrospective cross-sectional analysis, with the following objectives: to methods previously reported.…”
mentioning
confidence: 99%